Pregnancy after aortic root replacement in Loeys–Dietz syndrome: High risk of aortic dissection. Issue 8 (29th April 2016) - Braverman, Alan C.; Moon, Marc R.; Geraghty, Patrick; Willing, Marcia; Bach, Christopher; Kouchoukos, Nicholas T.
Abstract : Loeys–Dietz syndrome due to mutations in TGFBR1 and 2 is associated with early and aggressive aortic aneurysm and branch vessel disease. There are reports of uncomplicated pregnancy in this condition, but there is an increased risk of aortic dissection and uterine rupture. Women with underlying aortic root aneurysm are cautioned about the risk of pregnancy‐related aortic dissection. Prophylactic aortic root replacement is recommended in women with aortopathy and aortic root dilatation to lessen the risk of pregnancy. There is limited information in the literature about the outcomes of pregnancy after root replacement in Loeys–Dietz syndrome. We present a case series of three women with Loeys–Dietz syndrome who underwent elective aortic root replacement for aneurysm disease and subsequently became pregnant and underwent Cesarean section delivery. Each of these women were treated with beta blockers throughout pregnancy. Surveillance echocardiograms and noncontrast MRA studies during pregnancy remained stable demonstrating no evidence for aortic enlargement. Despite the normal aortic imaging and careful observation, two of the three women suffered acute aortic dissection in the postpartum period. These cases highlight the high risk of pregnancy following aortic root replacement in Loeys–Dietz syndrome. Women with this disorder are recommended to be counseled accordingly. © 2016 Wiley Periodicals, Inc.